Species in the genus Bonomiella Conci, 1942 (Phthiraptera: Menoponidae) from Argentina and Chile - Cicchino, Armando C.; González-Acuña, Daniel Alfonso (Zootaxa, 2012)
Species of the genus Bonomiella Conci, 1942, are a parasitic on bird species belonging to the family Columbidae (Aves, Columbiformes). In the present study we redescribe the species Bonomiella columbae Emerson, 1957 from Argentinean specimens, and describe the new species B. zenaidae sp. nov. from Zenaida auriculata virgate Bertoni, 1901, and Z. auriculata auriculata (des Murs 1847) from Argentina and Chile. Descriptions include male and female diagnostic features, and also descriptions of nymphal instars II and III. Also, we include a full diagnosis of the genus Bonomiella and an annotated checklist of the six species known to date, with their respective hosts.